Factors Influencing the Concentrations of the Large Neutral Amino Acids in the Brain and in the CSF of Dogs After Portacaval Anastomosis. Issue 4 (1991) - Jonung, Torbjörn; Ramzy, Adel; Herlin, Per; Chance, William T.; James, J. Howard; Fischer, Josef E.
Abstract : Portal-systemic shunting of blood is associated with hyperammonemia, an increased glutamine concentration in brain, an altered plasma neutral amino acid pattern, and high levels of several of the large neutral amino acids in brain. Since some of these amino acids are precursors for neurotransmitters and for other potentially neuroactive substances, high CNS levels of these amino acids may contribute to the development of encephalopathy. In order to determine the relative importance of changes in brain glutamine levels and changes in competition among the neutral amino acids for blood-brain transport, we measured the concentrations of the large neutral amino acids in plasma, cisternal cerebrospinal fluid and in brain tissue from various regions of dogs after end-to-side portacaval shunt. Although the changes in CSF amino acid levels correlated partially with altered amino acid plasma competitor ratios, better correlations were observed with the elevation of CSF glutamine. These results suggest a model of blood-brain amino acid transport in which a high level of glutamine in brain extracellular fluid competes with other neutral amino acids for efflux from brain, thus raising brain amino acid levels after portalsystemic shunting